2010
DOI: 10.1159/000314331
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated Hemoglobin Is a Predictor of Major Adverse Cardiac Events after Drug-Eluting Stent Implantation in Patients with Diabetes Mellitus

Abstract: Objectives: Diabetes mellitus is associated with the risk of restenosis and mortality after coronary stenting, but the relation between glycosylated hemoglobin (hemoglobin A1c) and prognosis has not yet been fully elucidated in patients with diabetes mellitus. The purpose of this study was to evaluate whether hemoglobin A1c is associated with a risk of major adverse cardiac events (MACE) after successful drug-eluting stent (DES) implantation in patients with diabetes mellitus. Methods: In a retrospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 46 publications
2
26
1
5
Order By: Relevance
“…As discussed before, previous trials designed to answer this question were diverse and reached different conclusions [8,9,10,11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed before, previous trials designed to answer this question were diverse and reached different conclusions [8,9,10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a mixed pattern of results was shown regarding the ability of HbA 1c to predict outcomes in this patient population [8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown HbA1c to be associated with an increased risk of MACE after PCI in diabetic patients. 60,61 Further study is required to determine whether HbA1c is an independent predictor of progression of nontarget lesions in diabetic patients.…”
Section: Predictors Of Progression Of Clinical Nontarget Lesions Requmentioning
confidence: 99%
“…Interaction between AGEs and receptors for AGE participates in the development and acceleration of diabetic vasculopathy [2]. Glycated hemoglobin A 1c (HbA 1c ) has been widely recognized as a marker of glycemic control [3] and was used to estimate the degree of coronary artery disease (CAD) and the risk of major adverse cardiac events (MACE) after successful implantation of drug-eluting stents in patients with type 2 diabetes mellitus (T2DM) [4,5]. Glycated albumin (GA) accounts for almost 80% of the circulating glycated proteins in vivo and is related to the development and progression of vascular complications in diabetes [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%